Developing Students' Tolerance Character Based on Understanding of Divine Values and Unity - Aliya Rahmawati; Citra Cahyani; Nadhia Fatmawati (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Indonesia is an archipelagic country with a lot of cultural diversity and wealth. This is because the country of Indonesia has thousands of islands which are inhabited by various people who have different races, ethnicities, religions and ethnicities. The method used in this study uses qualitative research which analyzes fields that are currently developing, but there is still a real need for study literature that can support addressing issues of quality and thoroughness of research. The purpose of this research is to find out how the tolerance character of civics education in students maintains divine values and national unity at the elementary age level. The benefits of this research are very instrumental in the application of practice in learning Citizenship Education by providing understanding and application in a tolerance character lesson that is in accordance with national values. In the results of this study, the role of civics education in maintaining divinity and national unity is very necessary so that students can have an attitude of tolerance, mutual respect, and respect for every difference that exists in this nation.